UTILIZATION OF THE NEAR INFRARED REFLECTANCE SPECTRUM TECHNIQUE TO PREDICT THE CHEMICAL COMPOSITION OF GRASS AND LEGUMES MIXED FORAGE - MIRA, Rodrigo Távora (Scientia Agraria, 2000)
The Near Infrared Spectroscopy (NIRS) technique has been shown to be adequate to predict forages nutrient content. With the goal to evaluate the analysis system base on NIRS on the prediction of DM (Dry Matter ), CP (Crude Protein), ADF (Acid Detergent Fiber, NDF (Neutral Detergent Fiber), Ca, and P it was conducted a trial on Guarapuava County, Paraná State, Brazil. In this study 360 samples divided on 6 cuttings have been utilized, with intervals between cuttings of 61, 60, 57, 143, and 103 days, and cuttings height of 5 cm during a one year period. The samples were consisted of Lolium multiflorum, Trifolium repens, Trifolium pratense, and Lotus corniculatus on the winter, and native pasture on the summer. The samples were dried using a force-air convection oven at 65º C, and they were grinded in Willey grinder with 1.0 mm screen. The absorption spectra was obtained using a NR4500 monochromator instrument from NIRSystems, and the measurements were transformed into log of inverse reflectance (log(1/R)). For the purpose of calibration, the regression coefficients (R2) for DM, CP, ADF, NDF, Ca, and P were, respectively: 0.92, 0.92, 0.93, 0.97, 0.49, and 0.64, while the calibrations standard error were, respectively: 1.67, 0.58, 1.52, 1.15, 0.10, and 0.03. Based on the results of this experiment it was concluded that NIRS analysis can predict nutrient quality of the forages selected on this trial.